Laptops simplified - Shoup, Kate 1972- (Indianapolis, IN Wiley Pub, 2011)
A guide to laptop computers covers choosing the best laptop, running Windows, using common applications, building a media library, using a word processing program, exploring the Internet, networking, and security
Includes index
1 2
Keywords: Laptop computers